Control Sequence Ranking for Critical System Based on Health of Equipment Thanks to Choquet Integral - Bouaziz, Mohammed-Farouk; Marange, Pascale; Voisin, Alexandre; Petin, Jean-Francois (Frontiers in Artificial Intelligence, 2021)
This paper presents a ranking method of operating sequences based on the actual condition of complex systems. This objective is achieved using the health checkup concept and the multiattribute utility theory. Our contribution is the proposal of sequences ranking process using data and experts’ judgments. The ranking results in a decision-making element; it allows experts to have an objective and concise overall ranking to be used for decision making. A case study is presented based on an experimental platform; it allows us to compare two aggregation operators: the weighted mean and the Choquet integral.